Revolution in glaucoma treatment: a review elucidating canaloplasty and gonioscopy-assisted transluminal trabeculotomy as modern surgical alternatives - Cwiklińska-Haszcz, Agnieszka; Gołaszewska, Kinga; Żarnowski, Tomasz; Kosior-Jarecka, Ewa; Konopińska, Joanna (Frontiers in Medicine, 2025)
Open-angle glaucoma (OAG) is a leading cause of permanent blindness worldwide, and surgical interventions that restore the natural aqueous humor outflow pathway have emerged as promising treatment options. Therefore, we aimed to analyze the efficacy and safety profile of specific antiglaucoma surgeries, namely canaloplasty (ab interno and ab externo techniques) and gonioscopy-assisted transluminal trabeculotomy (GATT), in surgical treatment patients with primary and secondary OAG. Consequently, a systematic review of the recent literature was conducted using online databases. The effectiveness of the surgeries was assessed by reductions in intraocular pressure (IOP) measurements and decreased use of antiglaucoma eye drops preoperatively and postoperatively. The safety profile of these procedures was evaluated by recording the incidence of specific intraoperative and postoperative complications. Independent studies have shown that ab interno and ab externo canaloplasty procedures and GATT effectively lower IOP and decline medications burden. Therefore, given the favorable safety profiles, canaloplasty and GATT are associated with low incidences of postoperative adverse events and exhibit comparable safety characteristics. However, additional research, including a well-conducted randomized controlled trial comparing ab externo and ab interno canaloplasty with GATT, is required to validate our findings.